Evaluating investment decisions based on the business cycle: A South African sector approach - Johnny Jansen van Rensburg; Gary Van Vuuren (Cogent Economics & Finance, 2020)
Sector investing aims to guide investors in identifying undervalued securities. Knowing which sectors flourish at different phases of the business cycle, investment returns may be boosted by increasing holdings in securities from strengthening sectors and reducing holdings in weakening ones. As the business cycle phase changes, security rotation can continuously improve portfolio returns. Sector investing is, however, heavily dependent upon accurate phase identification and therefore highly vulnerable to phase misidentification. Investing in securities which do not thrive at the phase identified could lead to inferior portfolio returns or even losses. There is ample precedent in the literature regarding the usefulness of Fourier analysis in identifying business cycle frequencies. This article contributes by installing this approach for the first time to augment existing sector investing methodology. We confirm that the sector rotation approach does generate statistically significant outperformance (relative to local market index performance) in South Africa. This work adds to the current dearth of theoretical and empirical research regarding sector rotation in emerging economies, so it can also be beneficial for researchers interested in similar milieus.
Keywords: C52; G11; 330; business cycle; efficient frontier; Fourier analysis; sector investing